Mācīšanās rezultātu nozīme profesionālās vidējās izglītības vadībā - Kinta, Gunta (Latvijas Universitāte, 2014)
Promocijas darba „Mācīšanās rezultātu nozīme profesionālās vidējās izglītības vadībā” mērķis ir izpētīt mācīšanās rezultātu nozīmi profesionālajā vidējā izglītībā un noskaidrot, kā notiek pāreja uz mācīšanās rezultātos balstītu izglītības procesu. Pētījuma ietvaros tika veikta profesionālās izglītības iestāžu audzēkņu aptauja, skolotāju un darba devēju intervijas. Pētījumā secināts, ka skolotāji un darba devēji neizprot mācīšanās rezultātu lomu profesionālajā izglītībā. Skaidri formulēti mācīšanās rezultāti profesionālās izglītības programmās sniedz precīzu informāciju par mācību procesu un tā iznākumu visām iesaistītajām pusēm, līdz ar to vairāk jauniešu var izvēlēties profesionālās izglītības programmas atbilstoši savām vajadzībām un interesēm, un darba devēji ir informēti, kādas ir absolventu zināšanas, prasmes un kompetences.

The aim of Thesis is to explore the meaning of learning outcomes in vocational upper-secondary education management and clarify how the shift towards education process and assessment of student achievement based on learning outcomes occurs. Learning outcomes are statements describing what a learner knows, understands and is able to do when completing a certain period of learning. Thesis outlines the development of learning outcomes approach to education, as well as theoretical principles underpinning the concept of learning outcomes. To analyse more thoroughly the term of learning outcomes, vocational education systems of Latvia, Estonia, England, Scotland, Germany, Ontario Province of Canada and Australia were explored in the context of learning outcomes and their elements. In the empirical study, survey of vocational education students, interviews with teachers and employers were conducted. Conclusions were drawn that teachers and employers do not understand the concept and use of learning outcomes in vocational education. Clearly formulated learning outcomes in vocational education programmes provide more precise information about learning and teaching process and its output for all stakeholders. As a result more young people are able to choose vocational education programmes according to their needs and interests, and employers are informed about graduates’ knowledge, skills and competences. Prior introducing learning outcomes approach to education, informative and educational measures for vocational education stakeholders should be arranged in order to promote a common understanding of meaning of learning outcomes. According to the results of study, the author elaborated: practical recommendations about the development of learning outcomes and relevant assessment criteria in vocational education; parts of an experimental vocational upper-secondary education programme including learning outcomes; scenario on the shift towards vocational education process and assessment based on learning outcomes.
Meaning of Learning Outcomes in Vocational Upper-Secondary Education Management
Keywords: Izglītības vadība; mācīšanās rezultāti; profesionālā vidējā izglītība; izglītības pievilcība; izglītības iestāžu efektivitāte; audzēkņu mācību motivācija; Education management; learning outcomes; vocational upper-secondary education; attractiveness of education; efficiency of education establishments; student learning motivation; assessment of student achievement